The New Jersey colony - Fradin, Dennis B.; Burnett, Robert B. (Chicago : Childrens Press, 1991)
Examines the history of the New Jersey colony from its beginnings to its achievement of statehood after the Revolutionary War. Includes profiles of significant individuals such as Lewis Morris, the Reverend John Witherspoon, and Molly Pitcher.
Includes index.
Keywords: New Jersey -- History -- Biography -- Juvenile literature. -- Colonial period, ca. 1600-1775; New Jersey -- History -- Juvenile literature. -- Revolution, 1775-1783; New Jersey -- History -- Biography -- Juvenile literature. -- Revolution, 1775-1783; New Jersey -- History -- Colonial period, ca. 1600-1775.; New Jersey -- History -- Biography. -- Colonial period, ca. 1600-1775; New Jersey -- History -- Revolution, 1775-1783.; New Jersey -- History -- Biography. -- Revolution, 1775-1783; New Jersey -- History -- Colonial period, ca. 1600-1775